Effect of altitude and harvest year on nutraceutical characteristics of Rubus ellipticus fruits - Dhatwalia, Jyoti; Kumari, Amita; Guleria, Ishita; Kumar Shukla, Rakesh; Saleh, Na’il; El-Nashar, Heba A. S.; El-Shazly, Mohamed (Frontiers in Nutrition, 2024)
Rubus ellipticus Smith is an evergreen shrub in the Rosaceae family, commonly known as yellow Himalayan raspberry. The objective of this study is to determine the morphological analysis, minerals, proximate, ascorbic acid, anthocyanins, and carotenoids content in R. ellipticus fruits.The fruit samples were collected from four different sites with different altitudes [500 m (District Bilaspur), 1000 m (District Hamirpur), 1500 m (District Solan) and 2000 m (District Shimla)] of Himachal Pradesh for the two consecutive years (2018 & 2019). The fruit morphological investigation revealed that the maximum length (7.71 ± 0.08 mm), width (8.71 ± 0.03 mm), and weight (0.80 ± 0.01 g) of fruits is achieved at higher altitudes (2000 m) in the year 2018 as compared to 2019. The mineral content (0.05-36.6 mg/g DW), ascorbic acid content (14.59-23.64 mg/g DW), proteins (95.20-131 mg/g DW), and crude fibers (5.6-11.5%) were also higher in fruits grown at 2000 m altitude, whereas carbohydrates (210-398 mg/g DW), crude fat (2.4-4.1%), and anthocyanins (0.42-1.35 mg/100g FW) contents were higher in fruits collected from 500 m altitude. According to the results, R. ellipticus fruits were rich in crude fiber, moisture, carbohydrates, protein, ash, and crude fat, as well as in micronutrients, and displayed significant variation with altitude in nutrient content. This could be due to the different environmental, geographical, and weather conditions. The high nutrient content of R. ellipticus suggests its future potential applications for the food and pharmaceutical industry.